Developmental trends in headache: an Italian school-based study of age- and gender-related changes in clinical characteristics and burden from childhood to adolescence - Federico Salfi; Gennaro Saporito; Simone Cesarano; Federica Guerra; Pamela Silva; Dina Di Giacomo; Elisabetta Tozzi; Michele Ferrara; Bruno Colombo; Francesca Pistoia (Therapeutic Advances in Neurological Disorders)
Background: Pediatric headache disorders are a significant public health issue, affecting school performance, social participation, and quality of life. Objective: Our aim was to explore the age- and gender-related changes in the characteristics and burden of headaches from childhood to adolescence, with a focus on diagnostic shifts, frequency, intensity, and quality-of-life. Design: We conducted a cross-sectional survey on five primary and secondary schools in the L’Aquila district, Italy. Methods: Using the translated Italian version of the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation questionnaire, we collected data on headache frequency, intensity, duration, associated symptoms, and impact. Diagnoses were algorithmically assigned through International Classification of Headache Disorders, 3rd edition criteria. Statistical analyses examined the effects of age, gender, and their interaction on clinical and quality-of-life outcomes. Results: In total, 431 students were included (mean age: 9.82 ± 2.28 years; range: 6–15; 52.9% female). Findings indicated that as children grow older, headaches become increasingly frequent, longer in duration, and more intensely experienced. The progression from primary to secondary school was accompanied by a transition in diagnosis, with undifferentiated headaches giving way to more specific categories, such as probable or definite migraine and, to a lesser extent, tension-type headache. Age-by-gender interactions revealed that older females experienced greater frequency and a more pronounced impact, while headache frequency affected quality of life with increasing age. Conclusion: Findings highlight gender-specific developmental trends in headache, characterized by increased frequency, intensity, and diagnostic clarity from childhood to adolescence. The burden of headache, particularly among older students, underscores the need for early recognition and age-appropriate interventions.